2021
DOI: 10.36909/jer.emsme.13879
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MoS2 as a Buffer Layer on CdTe Photovoltaic Cell Through Numerical Simulation

Abstract: A thin film based Cadmium Telluride photovoltaic cell is becoming highly competitive in the electric power industry. The major problem with the CdTe photovoltaic cell is the large barrier height behind the rear contact surface that prevents the solar cell to reach notional efficiency of 32%. A buffer layer is added to get a better result in terms of efficiency by reducing the valence barrier height at the rear contact surface of the CdTe photovoltaic cell. This manuscript presents the numerical simulation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The work successfully developed a solar cell with MoS 2 back contact, reaching a maximum PCE of 13.7%. The numerical modeling of the MoS 2 buffer layer for a CdTe solar cell was done by Singh et al…”
Section: Back Contactmentioning
confidence: 99%
See 1 more Smart Citation
“…The work successfully developed a solar cell with MoS 2 back contact, reaching a maximum PCE of 13.7%. The numerical modeling of the MoS 2 buffer layer for a CdTe solar cell was done by Singh et al…”
Section: Back Contactmentioning
confidence: 99%
“…The work successfully developed a solar cell with MoS 2 back contact, reaching a maximum PCE of 13.7%. The numerical modeling of the MoS 2 buffer layer for a CdTe solar cell was done by Singh et al 138 Bastola et al studied the possibility of using Ni-doped iron pyrite as the back-contact buffer layer between Cu and Au. 139 The work manipulated the p-type properties of iron pyrite by doping with Ni.…”
Section: Back Contactmentioning
confidence: 99%
“…The theoretical investigations on MoS 2 based solar cells are reported by many researchers in literature [36][37][38][39][40]. For instance, Ali et al [41] demonstrated Al/ITO/TiO 2 /MoS 2 /In 2 Te 3 /Ni solar cell to attain an efficiency of 33.32%.…”
Section: Introductionmentioning
confidence: 99%